Voltage‐operated potassium (Kv) channels contribute to endothelium‐dependent vasorelaxation of carvacrol on rat aorta. (23rd June 2016) - Testai, Lara; Chericoni, Silvio; Martelli, Alma; Flamini, Guido; Breschi, Maria Cristina; Calderone, Vincenzo
Abstract: Objectives: Carvacrol, a monoterpene widely present in nature, is commonly used in the food industry and in cosmetics, besides to possess a plethora of pharmacological properties, among these also in vitro vasorelaxing effects and in vivo hypotensive responses. Although in rat aortic rings carvacrol evoked a vasodilatation both in the presence and in the absence of endothelium, in preparations with intact endothelial layer its vasoactive response markedly improved. Methods: This study aimed at investigating the mechanism of action responsible for the endothelial component of the carvacrol‐induced vasorelaxing response observed in rat isolated aortic rings. Key findings: Pharmacological characterization led us to exclude the involvement of NO pathway (neither L‐NAME, NO biosynthesis inhibitor, nor ODQ, guanylate cyclase inhibitor, was able to modify the vascular effects of carvacrol) and of arachidonic acid cascade (no inhibitor intercepting the cascade influenced the endothelial‐dependent vasodilatation of the monoterpene). Moreover, endothelial TRP channels were also not involved, as capsazepine did not antagonize vasorelaxing effect. Finally, endothelial potassium channels were considered as possible targets of carvacrol; indeed, two voltage‐operated potassium (Kv) channel blockers, 4‐aminopyridine and quinine, significantly reduced carvacrol potency and efficacy indices. Conclusions: Kv channels seem to be responsible for vascular effects of the monoterpene typical of Labiatae family.